The Interplay of Leptin, Inflammation, and Obesity: A Comprehensive Review - Hemali Jha; Ishaan Tyagi; Sylvester Noeldoss Lazarus; Anamika Chakraborty Samant; Jitendra Patel (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
Obesity has become a global health concern, with its prevalence rising dramatically in recent decades. This book chapter examines the complex relationship between leptin, inflammation, and obesity, synthesizing current research to provide a comprehensive understanding of their interconnected roles in metabolic health. Leptin’s crucial function in regulating energy balance and metabolism was first explored, highlighting its connection to adipose tissue mass and its impact on appetite control and energy expenditure. This book chapter delves into the inflammatory aspects of obesity, discussing how excess adipose tissue contributes to a chronic low-grade inflammatory state, which in turn leads to various metabolic dysfunctions and related health complications. A key focus is placed on the dual role of leptin as both a metabolic regulator and a pro-inflammatory cytokine, elucidating how leptin dysregulation links obesity to inflammation and subsequent metabolic disorders. The chapter also considers the implications of leptin resistance in obesity and its contribution to sustained inflammation. Finally, potential therapeutic targets emerging from this intricate interplay were discussed, offering perspectives on managing obesity-related complications through interventions targeting leptin signaling and inflammatory pathways. This comprehensive analysis aims to enhance our understanding of the leptin-inflammation-obesity axis and its significance in developing effective strategies for obesity management and prevention of associated metabolic disorders.